Bordetella Adenylate Cyclase Toxin Inhibits Monocyte-to-Macrophage Transition and Dedifferentiates Human Alveolar Macrophages into Monocyte-like Cells - Ahmad, Jawid Nazir; Holubova, Jana; Benada, Oldrich; Kofronova, Olga; Stehlik, Ludek; Vasakova, Martina; Sebo, Peter (mBio, 2019)
Monocytes arriving at the site of infection differentiate into functional effector macrophages to replenish the resident sentinel cells. Bordetella pertussis, the pertussis agent, secretes an adenylate cyclase toxin-hemolysin (CyaA) that binds myeloid phagocytes through complement receptor 3 (CD11b/CD18) and swiftly delivers its adenylyl cyclase enzyme domain into phagocytes. This ablates the bactericidal capacities of phagocytes through massive and unregulated conversion of cytosolic ATP into the key signaling molecule cAMP. We show that exposure of primary human monocytes to as low a concentration as 22.5 pM CyaA, or a low (2:1) multiplicity of infection by CyaA-producing B. pertussis bacteria, blocks macrophage colony-stimulating factor (M-CSF)-driven differentiation of monocytes. CyaA-induced cAMP signaling mediated through the activity of protein kinase A (PKA) efficiently blocked expression of macrophage markers, and the monocytes exposed to 22.5 pM CyaA failed to acquire the characteristic intracellular complexity of mature macrophage cells. Neither M-CSF-induced endoplasmic reticulum (ER) expansion nor accumulation of Golgi bodies, mitochondria, or lysosomes was observed in toxin-exposed monocytes, which remained small and poorly phagocytic and lacked pseudopodia. Exposure to 22.5 pM CyaA toxin provoked loss of macrophage marker expression on in vitro differentiated macrophages, as well as on primary human alveolar macrophages, which appeared to dedifferentiate into monocyte-like cells with upregulated CD14 levels. This is the first report that terminally differentiated tissue-resident macrophage cells can be dedifferentiated in vitro The results suggest that blocking of monocyte-to-macrophage transition and/or dedifferentiation of the sentinel cells of innate immunity through cAMP-elevating toxin action may represent a novel immune evasion strategy of bacterial pathogens.IMPORTANCE Macrophages are key sentinel cells of the immune system, and, as such, they are targeted by the toxins produced by the pertussis agent Bordetella pertussis The adenylate cyclase toxin (CyaA) mediates immune evasion of B. pertussis by suspending the bactericidal activities of myeloid phagocytes. We reveal a novel mechanism of potential subversion of host immunity, where CyaA at very low (22 pM) concentrations could inhibit maturation of human monocyte precursors into the more phagocytic macrophage cells. Furthermore, exposure to low CyaA amounts has been shown to trigger dedifferentiation of mature primary human alveolar macrophages back into monocyte-like cells. This unprecedented capacity is likely to promote survival of the pathogen in the airways, both by preventing maturation of monocytes attracted to the site of infection into phagocytic macrophages and by dedifferentiation of the already airway-resident sentinel cells.
Keywords: interakce hostitele a patogenu; Bordetella pertussis; Cell Differentiation; Humans; adenylátcyklasový toxin; Host-Pathogen Interactions; alveolární makrofágy; Monocytes; Macrophages, Alveolar; monocyty; lidé; buněčná diferenciace; Adenylate Cyclase Toxin